2012
DOI: 10.1111/j.1349-7006.2012.02304.x
|View full text |Cite
|
Sign up to set email alerts
|

NIH3T3 cells overexpressing CD98 heavy chain resist early G1 arrest and apoptosis induced by serum starvation

Abstract: CD98 is a heterodimeric glycoprotein of 125‐kDa, which consists of a 90‐kDa heavy chain (hc) subunit and 35‐kDa to 55‐kDa light chain (lc) subunits. It is strongly expressed on the surface of proliferating normal cells and almost all tumor cells. To investigate the participation of CD98 in cellular proliferation and malignant transformation, we analyzed cell‐cycle progression of NIH3T3 clones transfected with cDNA of human CD98hc. Although NIH3T3 and control transfectant cells grown to the subconfluent state w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…CD98 is a heterodimer comprising heavy and light chains. The heavy chain binds to β-integrin and plays an important role in integrin signal amplification, cell proliferation, survival, migration, and adhesion [20][21][22], and the light chain is an amino acid transporter LAT1 that maintains rapid cell proliferation and enhanced intracellular metabolism in cancer cells. In this context, CD98hc functions as a co-factor stabilizing LAT1 and xCT [23].…”
Section: Ho-1-u-1 Sa3mentioning
confidence: 99%
“…CD98 is a heterodimer comprising heavy and light chains. The heavy chain binds to β-integrin and plays an important role in integrin signal amplification, cell proliferation, survival, migration, and adhesion [20][21][22], and the light chain is an amino acid transporter LAT1 that maintains rapid cell proliferation and enhanced intracellular metabolism in cancer cells. In this context, CD98hc functions as a co-factor stabilizing LAT1 and xCT [23].…”
Section: Ho-1-u-1 Sa3mentioning
confidence: 99%
“…(Cantor and Ginsberg, 2012). Originally described by Haynes et al in 1981 as an antigen on proliferating lymphocytes (Haynes et al, 1981), CD98 has since been shown to be overexpressed in human embryonic stem cells and various carcinoma cell lines (Hara et al, 2012). Additional work using monoclonal antibodies against CD98 revealed a role in proliferation of cancer cell lines that is propagated via the activity of the PI3K/AKT/mTOR pathway (Feral et al, 2005;Masuko et al, 2011).…”
Section: Dear Editormentioning
confidence: 99%
“…2A . Previous studies have shown that serum starvation can effectively induce cell apoptosis ( 32 , 33 ). In the current study, serum starvation conditions were induced on cultured mast cells for 24 h in order to initiate cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%